Globalization and Cultural Self-Awareness - Fei, Xiaotong (Springer, 2015)
This volume comprises some twenty articles, speeches and conversations of Fei Xiaotong from the late 1980s to the early 2000s. Their central connecting theme is how civilizations could co-exist against a backdrop of rapid globalization. Fei proposes his concept of “cultural self-awareness,” summarized in the axiom “each appreciates his own best, appreciates the best of others, all appreciate the best together for the greater harmony of all.” This is the result of many years of research and fieldwork, and represents a synthesis of his Western training and traditional Chinese thought.